Effects of temperature and nutrients on changes in genetic diversity of bacterioplankton communities in a semi-closed bay, South Korea. Issue 1 (15th May 2016) - Kim, Hyun Jung; Jung, Seung Won; Lim, Dhong-Il; Jang, Min-Chul; Lee, Taek-Kyun; Shin, Kyoungsoon; Ki, Jang-seu
Abstract: Bacterioplankton communities in a semi-closed bay (Jangmok Bay, South Korea) were analysed using a 16S rDNA multiplex 454 pyrosequencing approach. Diversity and operational taxonomic units of bacterioplankton communities in the Jangmok Bay are highest in cold water seasons and lowest in warm water ones. During cold seasons, α -proteobacteria respond rapidly to pulses of the concentration of inorganic nutrients, while γ -proteobacteria during warm water seasons are the most active type of bacterioplankton resent in the prevailing conditions, which include high dissolved organic carbon, chemical oxygen demand and primary production. Cyanobacteria, a minor group constituting 4.58% of the total bacterioplankton, are more abundant at low temperature. Flavobacteria are more abundant in nutrient-rich conditions and the abundance of this group also demonstrated a delayed decline following summer phytoplankton blooms. The pronounced seasonal oscillations in phosphorus concentration and temperature exert strong selection pressure on bacterioplankton communities. Highlights: Diversity and Operational Taxonomic Units of bacterioplankton are highest in cold water seasons. α- proteobacteria in cold seasons respond rapidly to pulses of the inorganic nutrients. γ- proteobacteria in warm seasons are the most active type of bacterioplankton present. Cyanobacteria are more abundant at low temperatures. Cytophaga-Flavobacteria group is more abundant in nutrient-rich conditions.